The Effect of Task-Based Language Teaching on Students’ Oral Communication Skills in EFL Classroom - Sualih Mussa Akalu (Journal of English Education, 2020)
The purpose of this study was to investigate the effect of context specific task-based language teaching approach on students’ oral communication skills. The study was conducted on grade 9 students of Addisalem Secondary school which is found in northern Ethiopia. For this purpose, quasi-experimental research design was employed. Two sections which contained 92 grade 9 students were selected using purposive sampling technique based on similarity of group identification test score. After identifying the control and experimental groups, speaking test (pre-and post-test) and students’ questionnaire (for experimental groups only) were used to get data. To test the reliability of the speaking test, Cronbach’s alpha was calculated. The internal consistency of the questionnaire gained from 27 pilot group students was 0.783. Thus, the tools of this study were reliable. The validity of the treatment manual, the pre-test and the post-test were also evaluated by two well experienced EFL teachers in a nearby school. T-tests were run to compare the improvement between and within groups. When we see the findings of the study, the paired sample t-test result revealed that the experimental group students showed a progress in their oral communication proficiency after the treatment. There was statistically significant differences at (sig.2-tailed=0.000) between the mean scores of the experimental group on the speaking pre-test and post-test. Again, the result of the independent sample t-test indicated that there were statistically significant differences  (sig.2-tailed=0.000) between the mean scores of the experimental group exposed to the designed context specific task-based program, and the control group receiving the tasks in the text book on the post-test in oral communication proficiency. Moreover, the result of experimental group students' questionnaire showed that task-based instruction had a positive impact on students' oral communication skill, as well. Finally, based on the findings of the study, the researchers forwarded ideas to improve the students’ oral communication.Key words: task based, oral communication, effect